PERANCANGAN KOMIK DIGITAL WEBTOON “THE STORY BEHIND DAMAR KURUNG” SEBAGAI MEDIA EDUKASI - Nova Ridho Sisprasojo; Riyandi Alamsyah; Izzati Winda Murti (Tanra: Jurnal Desain Komunikasi Visual Fakultas Seni Dan Desain Universitas Negeri Makassar, 2023)
Technological developments encourage people to think more creatively. Creativity can be expressed in various media, such as digital media which is more flexible to be accessed through devices. Likewise, the history of regional culture has important meaning but is not always easy to understand, especially by the younger generation. Through this research, researchers raised the history of the culture of Gresik Regency, East Java, which is known as Damar Kurung. The existence of Damar Kurung is well known to the public, but not all understand its history and cultural values of this. Therefore the authors designed digital media in the form of comics with the theme of Damar Kurung's cultural history. The method used by the author in this study includes the making aspect (observation and interview), the viewer aspect (questionnaire), and the image aspect (the author's view of the object under study). This comic is targeted the young generation, 15-25 years who live in Gresik. The outcome of this study is a webtoon digital comic "The Story Behind Damar Kurung” which tells about pieces of the history of Damar Kurung and also the stories of the characters in Damar Kurung.